Recent progress of nanomedicine in managing dry eye disease - Lv, Zeen; Li, Su; Zeng, Guixiang; Yao, Ke; Han, Haijie (Advances in ophthalmology practice and research, 2024)
Dry eye disease (DED) is a commonly reported ocular complaint that has garnered significant attention in recent research. The global occurrence of DED ranges from 5% to 50%, impacting a substantial proportion of individuals worldwide with increasing frequency. Although topical administration remains the mainstream drug delivery method for ocular diseases, it suffers from drawbacks such as low bioavailability, rapid drug metabolism, and frequent administration requirements. Fortunately, the advancements in nanomedicine offer effective solutions to address the aforementioned issues and provide significant assistance in the treatment of DED. DED is considered a multifactorial disease of the ocular surface and tear film, in which the integrity of tear film function and structure plays a crucial role in maintaining the homeostasis of the ocular surface. The conventional treatment for DED involves the utilization of artificial tear products, cyclosporin, corticosteroids, mucin secretagogues, and nonsteroidal anti-inflammatory drugs. Furthermore, nanomedicine is presently a significant field of study, with numerous clinical trials underway for various nanotherapeutics including nanoemulsions, nanosuspensions, liposomes, and micelles. Notably, some of these innovative nanoformulations have already received FDA approval as novel remedies for DED, and the advancement of nanomedicine is poised to offer enhanced prospects to solve the shortcomings of existing treatments for DED partially. This article provides an overview of the latest advancements in nanomedicine for DED treatment, while the field of DED treatment is expected to witness a remarkable breakthrough shortly with the development of nanomedicine, bringing promising prospects for patients worldwide suffering conditions.